Suicide Mortality Across Broad Occupational Groups in Greece: A Descriptive Study - Evangelos C. Alexopoulos; Katerina Kavalidou; Fani Messolora (Elsevier, 2016)
Background: Several studies have investigated the relationship between specific occupations and suicide mortality, as suicide rates differ by profession. The aim of this study was to investigate suicide mortality ratios across broad occupational groups in Greece for both sexes in the period 2000-2009. Methods: Data of suicide deaths were retrieved from the Hellenic Statistical Authority and comparative mortality ratios were calculated. Occupational classification was based on the International Classification of Occupations (ISCO-88) and the coding for Intentional self-harm (X60-X84) was based on the international classification of diseases (ICD-10). Results: Male dominant occupations, mainly armed forces, skilled farmers and elementary workers, and female high-skilled occupations were seen as high risk groups for suicide in a period of 10 years. The age-productive group of 30-39 years in Greek male elementary workers and the 50-59 age-productive group of Greek professional women proved to have the most elevated number of suicide deaths. Conclusion: Further research is needed into the work-related stressors of occupations with high suicide mortality risk and focused suicide prevention strategies should be applied within vulnerable working age populations.